Otorhinolaryngologic Manifestations of Long COVID-19 Infection Among Patients at the Quezon City General Hospital - Ma. Nina Kristine Sison; Emmanuel Tadeus Cruz (Philippine Journal of Otolaryngology Head and Neck Surgery)
Objective: To determine the otorhinolaryngologic manifestations of long COVID-19 infection among patients consulting at the Quezon City General Hospital.